Quantitative Physicochemical Analysis of Acid‐Base Balance and Clinical Utility of Anion Gap and Strong Ion Gap in 806 Neonatal Calves with Diarrhea. (March 2015) - Trefz, F.M.; Constable, P.D.; Lorenz, I.
Abstract : Background: Acid‐base abnormalities in neonatal diarrheic calves can be assessed by using the Henderson‐Hasselbalch equation or the simplified strong ion approach which use the anion gap (AG) or the strong ion gap (SIG) to quantify the concentration of unmeasured strong anions such asd ‐lactate. Hypothesis/Objectives: To determine and compare the clinical utility of AG and SIG in quantifying the unmeasured strong anion charge in neonatal diarrheic calves, and to examine the associations between biochemical findings and acid‐base variables by using the simplified strong ion approach. We hypothesized that the SIG provides a more accurate prediction of unmeasured strong anions than the AG. Animals: Eight hundred and six neonatal diarrheic calves admitted to a veterinary teaching hospital. Methods: Retrospective study utilizing clinicopathologic findings extracted from medical records. Results: Hyperphosphatemia was an important predictor of venous blood pH. Serum inorganic phosphorus and plasmad ‐lactate concentrations accounted for 58% of the variation in venous blood pH and 77% of the variation in AG and SIG. Plasmad ‐ and total lactate concentrations were slightly better correlated with SIG ( r s   = −0.69; −0.78) than to AG ( r s  = 0.63; 0.74). Conclusions and Clinical Importance: Strong ion gap is slightly better at quantifying the unmeasured strong anion concentration in neonatal diarrheic calves than AG. Phosphorus concentrations should be included as part of the calculation of A tot when applying the simplified strong ion approach to acid‐base balance to critically ill animals with hyperphosphatemia.